PROFESSIONAL TA’LIMDA KOMPETENTLI YONDOSHUV PRINSIPLARI ASOSIDA O‘QUVCHILAR MUSTAQIL ISHLARINI TASHKIL ETISHNING ASOSIY VAZIFALARI - Abidova, Z.K. (SCIENCE and SOCIETY, 2023)
The article considers the main tasks of the department for the effective organization of independent work of students on the basis of the implementation of the competence approach in professional education.
Keywords: competence; competent; independent work of a student; forms of independent work; strategic tasks; methodological tasks; management tasks